Vu Khoan [Vietnam, Deputy Prime Minister] - Khoan, Vu (Institutional Knowledge at Singapore Management University, 2017)
Vu Khoan, former Deputy Prime Minister for Vietnam, shares with DNA how he joined the foreign services, and then took charge of economic reform, where every assignment was a challenge that caused him to grow. He led Vietnam from political isolation to normalizing her international relations, especially with ASEAN countries. Interview and transcript in English and Vietnamese.